Lessons from the removal of lead from gasoline for controlling other environmental pollutants: A case study from New Zealand - Horrocks John; Wilson Nick (BMC, 2008)
Abstract Background It took over two decades to achieve the removal of leaded gasoline in this country. This was despite international evidence and original research conducted in New Zealand on the harm to child cognitive function and behaviour from lead exposure. Objective To identify lessons from the New Zealand experience of removing leaded gasoline that are potentially relevant to the control of other environmental pollutants. Discussion From the available documentation, we suggest a number of reasons for the slow policy response to the leaded gasoline hazard. These include: (1) industry power in the form of successful lobbying by the lead additive supplier, Associated Octel; (2) the absence of the precautionary principle as part of risk management policy; and (3) weak policymaking machinery that included: (a) the poor use of health research evidence (from both NZ and internationally), as well as limited use of expertise in academic and non-governmental organisations; (b) lack of personnel competent in addressing technically complex issues; and (c) diffusion of responsibility among government agencies. Conclusion There is a need for a stronger precautionary approach by policymakers when considering environmental pollutants. Politicians, officials and health workers need to strengthen policymaking processes and effectively counter the industry tactics used to delay regulatory responses.